Research on the Static Recrystallization and Precipitation Behaviors of a V-N Microalloyed Steel - Baochun Zhao; Tan Zhao; Guiyan Li; Qiang Lu (Advances in Materials Science and Engineering)
Double compression tests were performed on a Gleeble-3800 thermomechanical simulator to study the softening behaviors of deformed austenite in a V-N microalloyed steel. The static recrystallization volume fractions were calculated by stress offset method, and the kinetic model of static recrystallization was constructed. The effects of temperature, strain, and time interval on the softening behaviors were analyzed, and the interactions between precipitation and recrystallization were discussed. The results show that the softening behaviors of the deformed austenite at lower temperature or higher temperature are markedly different. At the temperature of 850°C or 800°C, pinning effects of the precipitates play the main role, and the recrystallization process is inhibited, which leads to the formation of plateaus in the softening curves. An increase in strain promotes the precipitation and recrystallization processes while reduces the inhibition effect of precipitation on recrystallization as well.